A feeling of nature in contemporary Norwegian picturebooks - Nina Goga (University of Bologna, 2017)
This article examines and discusses how children's literature, in particular four contemporary Norwegian picturebooks in which maps are provided, may help readers to connect, combine and relate their aesthetic reading experiences to their outdoor activities and, through this interrelation, develop or strengthen a feeling of nature that is necessary if one is to become an ecocitizen, aware of the need for a sustainable society. The analysis is informed by ecocriticism (Glotfelty 1996; Garrard 2012), and by writings that focus on the aesthetic representation of the idyll (Gifford 2014), the theory of literary maps (Goga 2015) and the theory of outdoor education (Presthus Heggen 2015). The investigation contributes to the research on nature in children's literature undertaken by the research group, Nature in Children's Literature and Culture (NaChiLitCul) at the Western Norway University of Applied Sciences.